The Living Room. : George Korsmit, Peer Veneman, Peter Kantelberg, Erik Andriesse, Kars Persoon, Frank Van den Broeck, Martin van Vreden, Henk Visch, Rob Scholte, Aldert Mantje, Harald Vlugt, Cecile Van der Heiden, Leo Mennen. - Nietzsche, Friedrich (Amsterdam, : The Living Room, 1983)
Korsmit, George ; Veneman, Peer ; Kantelberg, Peter ; Andriesse, Erik ; Persoon, Kars ; van den Broeck, Frank ; van Vreden, Martin ; Visch, Henk ; Scholte, Rob ; Mantje, Aldert ; Vlugt, Harald ; Heiden, Cécile Van Der ; Mennen, Leo
George Korsmit, Peer Veneman, Peter Kantelberg, Erik Andriesse, Kars Persoon, Frank Van den Broeck, Martin van Vreden, Henk Visch, Rob Scholte, Aldert Mantje, Harald Vlugt, Cecile Van der Heiden, Leo Mennen, The Living Room, Amsterdam, september 1983
Nederlands
boek